Association of Increased Epicardial Adipose Tissue Thickness With Adverse Cardiovascular Outcomes in Patients With Atrial Fibrillation. Issue 11 (March 2016) - Chu, Chun-Yuan; Lee, Wen-Hsien; Hsu, Po-Chao; Lee, Meng-Kuang; Lee, Hung-Hao; Chiu, Cheng-An; Lin, Tsung-Hsien; Lee, Chee-Siong; Yen, Hsueh-Wei; Voon, Wen-Chol; Lai, Wen-Ter; Sheu, Sheng-Hsiung; et al.
Abstract : Abstract: The thickness of epicardial adipose tissue (EAT) was reported to be highly associated with the incidence and severity of atrial fibrillation (AF). This study was conducted to analyze the ability of EAT thickness in predicting adverse cardiovascular (CV) events in AF. In 190 persistent AF patients, we performed a comprehensive transthoracic echocardiographic examination with assessment of EAT thickness. The definition of CV events included CV mortality, hospitalization for heart failure, myocardial infarction, and stroke. There were 69 CV events including 19 CV deaths, 32 hospitalizations for heart failure, 3 myocardial infarctions, and 15 strokes during a mean follow-up of 29 (25th–75th percentile: 17–36) months. The multivariable analysis demonstrates that chronic heart failure, increased left ventricular (LV) mass index and the ratio of transmitral E-wave velocity to early diastolic mitral annulus velocity, decreased body mass index, and increased EAT thickness (per 1-mm increase, odds ratio 1.224, 95% confidence interval [CI] 1.096–1.368, P  < 0.001) were associated with adverse CV events. Additionally, the addition of EAT thickness to a model containing CHA2 DS2 -VASc score, left atrial volume index, and LV systolic and diastolic function significantly improved the values in predicting CV events (global χ 2 increase 14.65, P  < 0.001 and integrated discrimination improvement 0.10, 95% CI 0.04–0.16, P  < 0.001). In AF, EAT thickness was useful in predicting adverse CV events. Additionally, EAT thickness could provide incremental value for CV outcome prediction over traditional clinical and echocardiographic parameters in AF.